2017
DOI: 10.1039/c7ra04907b
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of magnetically recyclable Co@BN core–shell nanocatalysts for catalytic reduction of nitroarenes

Abstract: The possible mechanism for Co@BN catalyzed 4-nitrophenol reduction in the presence of NaBH4. Moreover, the 13.6 wt% Co@BN core–shell nanoparticles exhibited the excellent catalytic activity in hydrogenation of nitroaromatic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…Significantly, dye degradation due to catalytic activity demonstrated best results in an alkaline environment which favorably supports our experimental findings. Several reports reveal that the highest dye degradation by catalytic activity was observed in an alkaline environment [61].…”
Section: Degradationmentioning
confidence: 99%
“…Significantly, dye degradation due to catalytic activity demonstrated best results in an alkaline environment which favorably supports our experimental findings. Several reports reveal that the highest dye degradation by catalytic activity was observed in an alkaline environment [61].…”
Section: Degradationmentioning
confidence: 99%
“…Subsequently, the chemisorption of 4‐NP onto carbon support occurs, causing the electrons and hydrogen species liberated from NaBH 4 to be carried to the nitrogen of the nitro group of 4‐NP to the carbon support. It can be observed that both reactants are adsorbed to the surface of the catalyst prior to the reaction, following the L‐H mechanism [74] . A transition surface complex of 4‐hydroxyl aminophenol is formed due to the transfer of electrons and active H species.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Zhang et al 92 prepared Pt−Pd nanoalloys supported on Fe 3 O 4 @C core−shell NPs using a facile two-step synthesis method (Figure 19) and characterized them by high-resolution TEM; Pt−Pd nanocatalyst decoration on a carbon layer coating on the surface of the Fe 3 O 4 NPs was discerned. In another exploration, Du et al 93 synthesized Pt−Pd NPs on super-paramagnetic core−shell nanocatalysts for the reduction of 4-NP to 4-AP using aqueous NaBH 4 . The hydrogenation required 22 min to completely convert the 4-NP to 4-AP using 13.63 wt % of the prepared nanocatalysts; the yield and selectivity were obtained to be 96% and 99%, respectively.…”
Section: Supported Magnetic Nanocatalystsmentioning
confidence: 99%